Governance in "Murky Waters": the Political Fields of Water Extractivism in Honduras (Alternautas, 2022)
Profound changes in public administration after the presidential elections in Honduras (2013) resulted in a re-structuring and regrouping of public institutions and autonomous entities for the relevant legislative period (2014-2018). These adjustments, thought as a “new public-private co-management” – aimed to “…tangible impacts not only within the administration but also within communities and scattered settlements which, in turn, are expected to be both, beneficiaries as well as participants in innovative sectorial and public policies programs.” The governments’ goal was to carry out a National Plan for Water and Sanitation (PLANASA, Plan Nacional de Agua y Saneamiento) together with a still pending financial sector policy for the WASH sector (CONASA, 2013b, c, 2014). Both politics established different mechanisms and instruments as well as strategic guidelines according to the Framework Law for Water and Sanitation (2003, FLWS, Ley Marco de Agua Potable y Saneamiento). New secretaries and institutional entities generated adjoined existing ones in their technical and administrative mandate.